1997
DOI: 10.1099/00221287-143-12-3693
|View full text |Cite
|
Sign up to set email alerts
|

Acetate acts as a protonophore and differentially affects bead movement and cell migration of the gliding bacterium Cytophaga johnsonae (Flavobacterium johnsoniae)

Abstract: Cells of Cytophaga johnsonae (now Hawobacterium johnsoniae) are able to translocate on solid surfaces but are unable to swim in liquid media. Organelles that may be involved in this gliding motility have not been detected, and the mechanism(s) responsible remains unknown. The movement of latex beads attached to the cell surface is considered by some to be a manifestation of the gliding machinery. In this study, acetate (in nutrient-level quantity, 45 mM) was found to inhibit bead movement on cell surfaces, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 26 publications
(42 reference statements)
0
17
0
Order By: Relevance
“…This was achieved effectively by using cyanide and azide as potent inhibitors of electron transport (Ridgway, 1977) : these are weak proton ionophores and cause a partial breakdown of the membrane potential (Harold, 1972(Harold, , 1977Duxburry et al, 1980 ;Dzink-Fox et al, 1997). Our data show for the first time the obvious impact of electron flow inhibition on surface features of actively gliding cells.…”
Section: Discussionmentioning
confidence: 78%
“…This was achieved effectively by using cyanide and azide as potent inhibitors of electron transport (Ridgway, 1977) : these are weak proton ionophores and cause a partial breakdown of the membrane potential (Harold, 1972(Harold, , 1977Duxburry et al, 1980 ;Dzink-Fox et al, 1997). Our data show for the first time the obvious impact of electron flow inhibition on surface features of actively gliding cells.…”
Section: Discussionmentioning
confidence: 78%
“…Previous studies indicated that proton motive force (PMF) powers gliding of Flavobacterium and related gliding bacteria (21)(22)(23)(24). To determine whether the SprB motion is powered by PMF, we examined the effects of carbonyl cyanide m-chlorophenylhydrazone (CCCP), a PMF uncoupler, on SprB motion.…”
Section: Resultsmentioning
confidence: 99%
“…The gliding motor converts chemical energy into mechanical work. Previous studies indicate that proton motive force (PMF) is required for gliding (12,34). ATP may also be needed, since it has been reported that cells depleted for ATP fail to propel latex spheres (12).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicate that proton motive force (PMF) is required for gliding (12,34). ATP may also be needed, since it has been reported that cells depleted for ATP fail to propel latex spheres (12). The motor presumably has one or more components that span the cytoplasmic membrane to harvest cellular energy.…”
Section: Discussionmentioning
confidence: 99%